Alterations in anterior cingulate cortex myoinositol and aggression in veterans with suicidal behavior: A proton magnetic resonance spectroscopy study. (30th June 2018) - Sheth, Chandni; Prescot, Andrew; Bueler, Elliott; DiMuzio, Jennifer; Legarreta, Margaret; Renshaw, Perry F.; Yurgelun-Todd, Deborah; McGlade, Erin
Highlights: Myoinositol (mI)/H2O ratio is significantly higher in the anterior cingulate cortex (ACC) and posterior cingulate cortex (POC) of veterans with suicidal behavior (SB) compared to veterans without SB. mI/H2O ratio in the ACC positively correlates with measures of SB and aggression. Verbal aggression partially mediates the relationship between mI/H2O in the ACC and SB. Abstract: Studies investigating the neurochemical changes that correspond with suicidal behavior (SB) have not yielded conclusive results. Suicide correlates such as aggression have been used to explore risk factors for SB. Yet the neurobiological basis for the association between aggression and SB is unclear. Aggression and SB are both prevalent in veterans relative to civilian populations. The current study evaluated the relationship between brain chemistry in the anterior (ACC) and the posterior cingulate cortex (POC), as well as the relationship between aggression and SB in a veteran population using proton magnetic resonance spectroscopy ( 1 H-MRS). Single-voxel MRS data at 3 Tesla (T) were acquired from the ACC and POC voxels using a 2-dimensional J-resolved point spectroscopy sequence and quantified using the ProFit algorithm. Participants also completed a structured diagnostic interview and a clinical battery. Our results showed that the myoinositol (mI)/H2O ratio in the ACC and POC was significantly higher in veterans who reported SB when compared to veterans who did not. The two groups did not differ significantly with regard to other metabolites. Second, verbal aggression and SB measures positively correlated with mI/H2O in the ACC. Finally, verbal aggression mediated the relationship between mI/H2O in the ACC and SB.